Representasi Wawasan Keindonesian dalam Buku Teks BIPA Sahabatku Indonesia: BIPA sebagai Soft Diplomacy untuk Memperkenalkan Indonesia: Representation of Indonesian Insights in The Textbook BIPA Sahabatku Indonesia: BIPA as a Soft Diplomacy to Introduce Indonesia - Aswan, Aswan; Susanto, Gatut (Balai Bahasa Provinsi Papua, 2024)
The BIPA Sahabatku Indonesia textbook is popular teaching material among the BIPA community. This is because of easy access to download and use it. Based on this context, this study aims to explore Indonesian insights from textbooks. As a book initiated by Language Development and Development Materials, the textbook has an urgency to be researched as a description of Indonesian content applied by the author of the book. The method used in this study was qualitative with a content analysis approach. The data for this research are seven series of my best-friend Indonesia textbooks uploaded on the official website of the BIPA Language Agency. Data analysis techniques were carried out through the stages of reading, marking, recording, rechecking, and revising. The analysis model used was interactive analysis. The results of the research are Indonesian insights, which are represented through 10 units in a series of textbooks. Each unit represents an Indonesian insight appropriate for the topic of discussion. The Indonesian insight is represented through authentic socio-cultural practices, art, literature, history, politics, education, environmental issues, and so on as Indonesian identity. These findings have implications for the concept that BIPA, which contains teaching materials, can be used as soft diplomacy to introduce Indonesia to the world community through BIPA learning, which contains Indonesian insights.